2020
DOI: 10.1038/s41398-020-00932-0
|View full text |Cite
|
Sign up to set email alerts
|

Applying dimensional psychopathology: transdiagnostic associations among regional homogeneity, leptin and depressive symptoms

Abstract: Dimensional psychopathology and its neurobiological underpinnings could provide important insights into major psychiatric disorders, including major depressive disorder, bipolar disorder and schizophrenia. In a dimensional transdiagnostic approach, we examined depressive symptoms and their relationships with regional homogeneity and leptin across major psychiatric disorders. A total of 728 participants (including 403 patients with major psychiatric disorders and 325 age-gender-matched healthy controls) underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…In the present study, MAM rats were observed to have significantly increased ReHo in the frontal regions and decreased ReHo in the posterior primary cortex, suggesting that frontal‐posterior functional imbalance may be the neurodevelopmental basis for MPDs. A series of our previous research using multiple neuroimaging modalities has consistently shown that increased frontal functional activity and decreased posterior functional activity are shared features across MPDs 34–37 . In addition, in our recent work, patients with MPDs who showed a frontal‐posterior functional imbalance had higher genetic vulnerability with increased Polygenic Risk Score for Schizophrenia and Bipolar Disorder (PRS‐SZBD) and enriched risk gene expression in brain regions including the frontal cortex, limbic system and basal ganglia 14 .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In the present study, MAM rats were observed to have significantly increased ReHo in the frontal regions and decreased ReHo in the posterior primary cortex, suggesting that frontal‐posterior functional imbalance may be the neurodevelopmental basis for MPDs. A series of our previous research using multiple neuroimaging modalities has consistently shown that increased frontal functional activity and decreased posterior functional activity are shared features across MPDs 34–37 . In addition, in our recent work, patients with MPDs who showed a frontal‐posterior functional imbalance had higher genetic vulnerability with increased Polygenic Risk Score for Schizophrenia and Bipolar Disorder (PRS‐SZBD) and enriched risk gene expression in brain regions including the frontal cortex, limbic system and basal ganglia 14 .…”
Section: Discussionmentioning
confidence: 84%
“…A series of our previous research using multiple neuroimaging modalities has consistently shown that increased frontal functional activity and decreased posterior functional activity are shared features across MPDs. 34 , 35 , 36 , 37 In addition, in our recent work, patients with MPDs who showed a frontal‐posterior functional imbalance had higher genetic vulnerability with increased Polygenic Risk Score for Schizophrenia and Bipolar Disorder (PRS‐SZBD) and enriched risk gene expression in brain regions including the frontal cortex, limbic system and basal ganglia. 14 These findings support our present result, highlighting that the genetic and neurodevelopmental factors contribute to the neuroimaging pattern of frontal‐posterior imbalance.…”
Section: Discussionmentioning
confidence: 89%
“…Depression impacts the anterior cingulate and insular cortices of the brain (Besteher et al, 2022;Kühn et al, 2021;Corbo et al, 2016). Additionally, the precuneus and temporal areas of the DFN were affected; however, not as significant as alterations within the cortices (Besteher et al, 2022;Wei et al, 2020).…”
Section: Theme 4 Depressionmentioning
confidence: 86%
“…The connectivity between neuron density and cell type may contribute to functional connectivity within a small region, and regional alterations in micro-level homogeneity most likely contribute to regional functional connectivity alterations (Jiang et al, 2015). Regional homogeneity (ReHo) is a highly reproducible and reliable index of regional functional connectivity (Jiang & Zuo, 2016), which has been considered to reflect anatomical, morphological, and intrinsically geometric features in a local brain structure as well as a topology-functionality interplay (Wei et al, 2020). Accumulating evidence implicates ReHo alterations in the pathophysiology of MPDs (Ji et al, 2020; Jiang et al, 2015; Zuo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%